Effect of annealing on silver oxide nano particle generated by electrochemical discharge machining. (2018) - Singh, Purushottam Kumar; Shubham,; Singh, Nirmal Kumar; Bishwakarma, Harish; Hussain, Manowar; Das, Alok Kumar; Prasad, B. Hari
Abstract: The structural and optical studies of silver oxide (Ag2 O) nanoparticles were generated through electrochemical discharge process. In this experiment synthesized Ag2 O NPs were annealed at different temperatures. The synthesized Ag2 O NPs were characterized by the X-ray diffraction analysis, Fourier-transform infrared spectroscopy (FTIR) and Field emission scanning electron microscopy (FESEM). The average crystal size of Ag2 O NPs increases with increase in annealing temperature. The morphology such as shape and size of nanoparticle were observed to be changed with increase of annealing temperature. A Plate type structure is obtained with high annealing temperature. The EDX spectra of silver oxide nanoparticles showed both signals of silver and oxygen which indicates generated nanoparticle is pure silver oxide.